State Aid and Export Competitiveness in the EU - Mario Holzner; Roman Stöllinger (The Vienna Institute for International Economic Studies (wiiw), 2013)
Despite the proclaimed return of industrial policy (Wade, 2012) state aid provided by EU Member States remains at a historically low level. This is partly explained by the unique institutional arrangement in the EU which empowers the European Commission to monitor and restrict state aid activities of Member States. Making use of European state aid statistics over the period 1995-2011 we employ an augmented macroeconomic export function to investigate the relationship between state aid for the manufacturing sector and Member States' export performance. With manufacturing value added exports serving as a proxy for export performance, our model suggests that a 10% increase in manufacturing aid increases exports by 0.67% for the average EU country. The result is confirmed by instrumental variable estimation. We also find that the impact of state aid on exports is increasing with government effectiveness leading to large differences in the leverage of aid expenditures to promote export performance across Member States.
Keywords: F13; L52; 330; industrial policy; state aid; value added exports; external competitiveness